FACEBOOK’S FEATURES AND THE IMPACT ON THE PURCHASE BEHAVIOR OF CONSUMERS OF ORGANIC PRODUCTS - GENERATION Y AND Z - Teixeira, E.; Lima, Ana; Teixeira, Sandrina (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2023)
In the era of digital globalization, there are many behavioral changes in consumption. Most social media users use them to search for information about a product to determine whether they want to proceed with the purchase. Therefore, companies must develop digital marketing strategies for their profiles on social networks, especially in competitive markets, such as organic products. The objective of this study is to understand whether Facebook’s features have an influence on the purchasing behavior of consumers of organic products and which of the features has the most impact on these individuals. A questionnaire was created to carry out this study, which received 205 responses. The results of the study showed a positive influence of the following Facebook features on the purchase behavior of consumers of organic products: the “like” button, the “share” button, and the “advertising” button. Furthermore, these features proved to be more influential on Generation Z.